Modulating the properties and structure of lignins produced by alkaline delignification of sugarcane bagasse pretreated with two different mineral acids at pilot-scale - Nunes da Silva, Vinicius Fernandes; Farias de Menezes, Fabricia; Gonçalves, Adilson Roberto [UNESP]; Martín, Carlos; de Moraes Rocha, George Jackson (Elsevier, 2024)
Sugarcane bagasse was pretreated with dilute phosphoric acid or sulfuric acid to facilitate cellulose hydrolysis and lignin extraction. With phosphoric acid, only 8 % of the initial cellulose was lost after delignification, whereas pretreatment with sulfuric acid resulted in the solubilization of 38 % of the initial cellulose. After enzymatic hydrolysis, the process using phosphoric acid produced approximately 35 % more glucose than that using sulfuric acid. In general, the lignins showed 95–97 % purity (total lignin, w/w), an average molar mass of 9500–10,200 g mol−1, a glass transition temperature of 140–160 °C, and a calorific value of 25 MJ kg−1. Phosphoric acid lignin (PAL) was slightly more polar than sulfuric acid lignin (SAL). PAL had 13 % more oxidized units and 20 % more OH groups than SAL. Regardless of the acid used, the lignins shared similar properties, but differed slightly in the characteristics of their functional groups and chemical bonds. These findings show that pretreatment catalyzed with either of the two acids resulted in lignin with sufficiently good characteristics for use in industrial processes.
Keywords: Acid pretreatment; Biorefinery; Lignin characterization; Sugarcane bagasse